Needs Analysis to Develop Physics Learning E-Modules on Static Electricity Material - Korry Nilyani; Hilmi Rizki Anjani; Desnita Desnita; Usmeldi Usmeldi (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
Science and technology continue to experience developments in education at the school level, giving rise to demands and improvements in the learning process. In the 21st century, students need the right learning resources in order to understand the lesson well. It is necessary to do a needs analysis to develop learning media. This study aims to analyze the need for e-module development for physics learning. The urgency of this research is due to the difficulties faced by students in understanding physics concepts and solving physics problems. The problem discussed in this study is the need for effective learning media that can improve learning outcomes and students' interest in physics. The solution proposed is the development of an e-module learning physics on static electricity that can help students understand concepts and improve problem solving and critical thinking skills. This type of research is qualitative descriptive research. Research data collection instruments in the form of a questionnaire analysis of teacher needs, and a questionnaire analysis of student needs. The results of this study are the use of learning media on static electricity material in the four schools is very low. They only rely on textbooks as the only source in the learning process, so that students in the four schools may experience limitations in the exposure of information and learning experiences. Limitations in the use of textbooks can hinder creativity, interactivity, and in-depth understanding in learning, so it is necessary to develop e-modules as learning media for this material.